2015
DOI: 10.1007/s11250-015-0963-8
|View full text |Cite
|
Sign up to set email alerts
|

Physiological changes in the peri-partum period and colostral IgG transfer in prolific D’man sheep: effects of parity and litter size

Abstract: The aim of this work was to assess maternal and neonatal changes in plasma proteins, glucose and cortisol and to quantify the colostral immunoglobulin G (IgG) transfer in the peri-partum period in D'man sheep, a prolific breed, taking into account the parity of the ewe. The concentrations of proteins and glucose were high in the ewes on day 7 and at lambing before decreasing. Likewise, cortisol plasma concentration was maximal during the 6 h following lambing and dropped at 12 h. Protein and glucose concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
0
6
3
Order By: Relevance
“…This variation with number of lambings did not achieve statistical significance. Our results suggest that colostrum quality is highest at the first lambing, which contrasts with other studies reporting higher IgG concentration in sheep colostrum from multiparous than primiparous ewes (Chniter et al 2016) or no variances (Alves et al 2015). This discrepancy may reflect differences in breed, nutrition, method of analysis, and method of colostrum collection.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…This variation with number of lambings did not achieve statistical significance. Our results suggest that colostrum quality is highest at the first lambing, which contrasts with other studies reporting higher IgG concentration in sheep colostrum from multiparous than primiparous ewes (Chniter et al 2016) or no variances (Alves et al 2015). This discrepancy may reflect differences in breed, nutrition, method of analysis, and method of colostrum collection.…”
Section: Resultscontrasting
confidence: 99%
“…The proportions of samples in our study meeting these cut-offs for high quality colostrum are smaller than the corresponding proportions reported for cattle (Bartier et al 2015). This may reflect loss of colostrum quality during the time from lambing to colostrum sampling: IgG concentration in sheep colostrum can drop by over 30% between 1 and 6 h post-delivery (Chniter et al 2016). Consistent with this possibility, mortality and morbidity of lambs bred artificially since birth were low throughout the study period.…”
Section: Resultsmentioning
confidence: 99%
“…The higher concentrations could also be due to larger energy reserves in higher birth-weight kids compared with the lower birth-weight kids, which can easily be mobilized to produce glucose endogenously. 11,49,54 In disagreement with the current study, Njidda et al reported higher blood glucose concentrations in older female kids than male kids of the RSG breed. 51 The high blood glucose levels in buck kids could be a metabolic response to cope with the higher physical activity associated with buck kids compared with doelings.…”
Section: Discussioncontrasting
confidence: 93%
“…Negative energy balance during the transition period has severe consequences for the metabolism, immune system, and performance of dairy cows (Esposito et al, 2014;Wankhade et al, 2017). In small dairy ruminants, few studies focusing on immune status around parturition (late pregnancy, partum, and early lactation) are available in the literature (Castro et al, 2006;Rodinova et al, 2008;Chniter et al, 2016). As described in dairy cows, the immune system is directly affected by negative energy balance around parturition (Esposito et al, 2014;Wankhade et al, 2017).…”
Section: Introductionmentioning
confidence: 99%